"En ganske anden Strandvej": Blichers vestkyst mellem betragtning og brug - Dejgaard, Jonas Ullerup (Passage - Tidsskrift for litteratur og kritik, 2026)
“Quite a Different Coastal Road” This article examines Steen Steensen Blicher’s literary portrayal of the west coast of Jutland. Through analyses of place, character, and narrative strategy in Blicher’s west coast literature, it argues that the west coast is framed both as landscape and workplace, thus forming a stark contrast to the Øresund shoreline made popular by the Romantic writers and painters of the time. Blicher’s texts pioneered the west coast’s inclusion in Danish literary geography.